Effects of Pasak reservoir on the flood levels of the lower Chao Phraya river from Ayutthaya to Bangkok - Surachai Laikarnchanapaiboon; Tawatchai Tingsanchali; Naritaka, Kubo; Harumichi, Kyotoh (Bangkok : Asian Institute of Technology, 1997)
The flood problems in the lower Chao Phraya river basin causes severe damages in the lower Chao Phraya flood plain and especially in Bangkok. The Pasak reservoir is constructed on the Pasak river for multipurpose including flood control, irrigation and water supply. The Pasak reservoir regulates the flood inflow and release the stored flood volume into the Pasak river before joining with the Chao Phraya river at Ayutthaya province. In this study, two mathematical models namely the HEC-5 model for reservoir flood control and water conservation system and the MIKE 11 hydrodynamic model for flood routing are used. The HEC-5 model is applied to route the design flood inflows of 100, 500 and 1,000 year return periods to downstream of the Pasak river. The MIKE-11 model is applied to route the release from the Pasak dam along the Pasak river to its confluence with the Chao Phraya river at Ayutthaya and from Ayutthaya along the Chao Phraya river through Bangkok to the river mouth at Fort Chula. The flood hydrographs at various station along both rivers are computed for the cases with and without the Pasak reservoir. The MIKE-11 model was calibrated successfully using the hourly flood data from 10 Sep to 30 Nov, 1987 and verified using the hourly flood data from 1 to 30 Nov, 1995. The results of model applications shown that the flood peak levels in the Pasak river are decreased by 0.27 m (at station S26) to 0.55 m (at station S9) along the river for the 500 year return period flood with a delay in the time to peak from 8-24 hours, and by 0.35 m (at station S26) to 0.68 m (at station S9) for the 1,000 year return period flood and the time delay in flood peak is about 1 day. For the Chao Phraya river, the effects of the Pasak reservoir on the flood peak levels is negligible due to small flood volume of the Pasak river (1000 year return period) compared to that of the Chao Phraya river of 20 year return period. However, there is a significant delay in the time to peak of 1 to 2 day due to the routing effect of the Pasak reservoir.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering. School of Civil Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1996
Keywords: Pasak Reservoir; Water levels -- Chao Phraya River